Xanthogranulomatous Endometritis with calculus formation in setting of prolapsed uterus - Nikhil Kumar,; Prima Shuchita Lakra,; Ranwir Kumar Sinha,; Asitava Deb Roy,; Debarshi Saha,; Jitendra Kumar Sinha, (Autopsy and Case Reports, 2023)
Xanthogranulomatous inflammation is a rare benign inflammatory lesion characterized by sheets of lipid-laden foamy histiocytes. It has been reported in various organs, mainly the kidney and gall bladder. Xanthogranulomatous endometritis (XGE) is sporadic, with only a few cases reported in the English medical literature. Herein, we report a case of xanthogranulomatous endometritis with the formation of stones in a 50-year-old female patient with a prolapsed uterus. Grossly the endometrium was irregular, and the uterine cavity was filled with a yellow friable material, a polypoid growth, and yellowish stones. The microscopy showed sheets of histiocytes with few preserved endometrial glands. In this case, the xanthogranulomatous inflammation may mimic a clear cell carcinoma involving the endometrium and myometrium. One of the important differential diagnoses is malakoplakia. Immunohistochemistry and special stains are helpful in diagnosis.